Software implementation of the Central Solar Battery Charging Station (CSBCS) - Chowdhury, Farhana; Shabnam, Farah; Islam, Farha R.; Azad, Dr. AKM Abdul Malek (© 2013 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2013 International Conference on Power, Energy and Control, ICPEC 2013; Dindigul; India; 6 February 2013 through 8 February 2013 [© 2013 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/ICPEC.2013.6527754